A collection of MATLAB scripts and functions for the processing of data from the TriOS Online Hyperspectral Integrating Cavity Absorption Meter (OSCAR) - Wollschläger, Jochen; Röttgers, Rüdiger; Zielinski, Oliver (PANGAEA, 2019)
The provided code is designed to evaluate data measured by the Online Hyperspectral Integrating Cavity Absorption Meter (OSCAR) manufactured by the company TriOS (Germany). Based on the raw light intensity spectra obtained by the instrument, the absorption coefficient spectra of a water sample are calculated, taking into account that the measurements are done with an integrating cavity (which eliminates errors associated with light scattering on particles). Besides the code itself, also two datasets for test purposes are provided (as the OSCAR provides two different data formats). Both sets include the light intensity spectra measured by the OSCAR (accompanied with the respective dark measurements) from calibration, reference, and sample measurements. Furthermore, an Excel file is provided that contains information about the time of the respective measurements and other information necessary for data processing (specified by the user). The samples in the "DAT" dataset are different solutions of humic acid, while in the "CSV" dataset a coastal water sample has been measured. Short instructions to use the code are given in the "Readme.txt". There, also the publications are cited that contain the original equations as well as the theoretical background of absorption coefficient determination with an integrating cavity. The most recent code version of the code can also be found under the following link: https://github.com/JochenWollschlaeger/OSCAR
Keywords: absorption; integrating cavity; MATLAB code